Bourgeois Knowledge: The Incomplete Closure of the Epistemological Break in the Work of Deirdre McCloskey - Erwin Dekker; Pavel Kuchař (Journal of Contextual Economics – Schmollers Jahrbuch, 2020)
One of the defining features of modern social science and economics in particular is the hard break it posits between everyday and scientific knowledge. French philosophers have called this characteristic the epistemological break. One of the key consequences of this break is that scientists have access to superior knowledge and are in a position to inform and steer the behavior of individuals. We believe that a large epistemological break is incompatible with science in a liberal democratic society. In this paper we analyze the extent to which the writings of Deirdre McCloskey contributed to bridging the epistemological break given that her early work, and the work of some members of younger Chicago School of economics more generally, was strongly influenced by the epistemological break. In the first decade after The Rhetoric of Economics McCloskey did much to strip scientific knowledge of its special elevated status. In her later work on the bourgeoisie there is also a renewed appreciation for everyday knowledge of economic actors. Yet important tensions remain, the appreciation for bourgeois knowledge has not been generalized to an appreciation for all everyday economic knowledge. And the tension between the economist as teacher, and the economist as student of society, which is already present in the Chicago tradition, is still visible.
Keywords: A13; A14; B41; Z13; 330; Epistemological Break; Deirdre McCloskey; Expert Knowledge; Everyday Knowledge; Bourgeoisie